Odpowiedzi

Najlepsza Odpowiedź!
2010-02-28T11:25:41+01:00
A) x-y=2
x+y=7

x=2+y
2+y+y=7

x=2+y
2y=5

x=2+y
y=2.5

x=2+2.5
x=4.5

spr.: x-y=2
4.5-2.5=2




b) 3x-y=5
2x+3y=1

-y=5-3x
2x+3y=1

y=-5+3x
2x+3y=1

y=-5+3x
2x+3(-5+3x)=1

y=-5+3x
2x-15+9x=1

y=-5+3x
11x=16

y=-5+3x
x=16/11
2010-02-28T11:26:39+01:00
A) x-y=2/ +y
x+y=7

x=2+y
2+y+y=7/-2

x=2+y
2y=5/:2

y=2,5
x=2+2,5

y=2,5
x=4,5

b) 3x-y=5/-3x
2x+3y=1

-y=5-3x /*(-1)
2x+3y=1

y=-5+3x
2x+3(-5+3x)=1

y=-5+3x
2x-15+9x=1/+15

y=-5+3x
11x=16 /:11

x=16/11
y=-5+3*16/11

x=16/11
y=-7/11

Liczę na naj ;)
2010-02-28T11:31:06+01:00
x-y=2
x+y=7

x=2+y
x+y=7

x=2+y
(2+y)+y=7

x=2+y
2+2y=7

x=2+y
2y=7-2

x=2+y
2y=5/:2

x=2+y
y=2.5

x=2+2.5
x=4.5


b))
3x-y=5
2x+3y=1

-y=5-3x/ x(-1)
2x+3y=1

y=-5+3x
2x+3y=1

y=-5+3x
2x+3(-5+3x)=1

y=-5+3x
2x-15+9x=1

y=-5+3x
11x=1+15

y=-5+3x
11x=16/:11
x=1,45

y=-5+3x
y=-5+3(1,45)
y= -5+4,36
y=-0,64